MAKNA DAN PESAN BERTATO (ANALISIS DESKRIPTIF KUALITATIF DALAM PANDANGAN PENGGUNA TATO DI STUDIO PRABOE JAZZ TATTOO YOGYAKARTA): makna dan pesan tatto - Mochammad Assad Fadlyan; Kristina Andryani (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
A  tattoo  is  an  art  of  body  painting  that  used  human  body  as  a  medium  to  expert  himself  or   herself.  Praboe  Jazz  Tattoo  Studio  is  one  of  tattoo  studios  located  in  Yogyakarta  concerned   with  art  tattoos.  This  place  has  been  around  since  1998.  This  place  can  be  considered  as  one   of  the  promoters  for  art  tattoos  to  be  known  and  expanded  in  Yogyakarta.  The  researcher   selects  this  place  for  conducting  the  data  of  the  study.  Four  informants  are  obtained  through   in-‐‑depth  observations  and  interviews.  The  result  show  that  for  most  part  of  people,  tattoos   can  represent  the  identity  of  their  user.  Also,  symbols  in  tattoos  for  some  extent  can  embody   a  certain  message  and  meaning  of  each  person  who  wear  them.  These  message  and  meaning   are  generally  formed  from  their  interaction  to  surroundings  that  become  a  self  concept.  In   this  case,  each  person  may  have  distinctive  self  concept.